Study on Physical Properties of Reduced Graphene Oxide from Heating Coconut Shell - Mas’udah Kusuma Wardhani; Fahmi Astuti; Darminto Darminto (Universitas Negeri Malang, 2016)
A research to determine the solar activity in the months from January to March 2015, and analyze the characteristics of flare on the rotation angle shifting of the sunspot group of sunspot sample observed, has been conducted. The method was observation and descriptive analysis of quantitative data. Determination of coordinates of sunspot was done using the software IDL. These observations were made in the Aerospace Observation Center (BPD) LAPAN Watukosek. Data were analyzed in the form of a sketch-owned BPD Sunspot LAPAN Watukosek, ie sunspot sketch of months from January to March in 2015 and the data was taken from NOAA. The results showed that the flare is not always the case in large class of sunspot groups, however, the small class was able to produce a flare. Most flares ware occur after experiencing a shift angle in the preceding or following although with angles that were not too large (<10 °). The highest solar activity was occurred in January 2015 with the appearance of a sunspot group consisting of as many as 130 in 1063 sunspots. DOI: 10.17977/um024v1i12016p001